The Influence of Disintegration Methods on Test Results for Assessment of the Soil Particle Size Distribution - Dana Sitanyiova (Communications - Scientific letters of the University of Zilina, 2001)
The article pertinent to the research activity focuses on the hydrometer test performed for assessment of the soil particle size distribution for soils not containing the particles of size over 2 mm. Some stages of the test seem to be problematic, and various laboratories often obtain different test results. The contribution is directed to prove the fact that various methods of particles separation substantially influence the result of a whole hydrometer test and trace how variousseparation methods effect the individual mineral particles together with dispersing agent.